2018
DOI: 10.1111/jam.14060
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of aflatoxin-detoxifying yeast and bacteria from ruminal fluids to reduce aflatoxin B1 contamination in dairy cattle feed

Abstract: The abilities of isolates to survive and be active in anaerobic and aerobic conditions rendered them to be active in cattle's rumen. Their biomass could be produced in bulk and used as feed supplement for aflatoxin detoxification in dairy cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
2
29
0
2
Order By: Relevance
“…Treatments consisted of control (no supplemental yeast), K. marxianus CPY1 (K1Y), K. marxianus RSY5 (K2Y) or P. kudriavzevii YSY2 (PY). These yeasts were previously identified to have the potential to effectively detoxify aflatoxin in vitro [27]. Supplemental yeasts were individually fed at the rate of 2 g/day (1 g provided 1 × 10 9 CFU) by mixing supplemental yeast with 20 g cornmeal based on our previous research [27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments consisted of control (no supplemental yeast), K. marxianus CPY1 (K1Y), K. marxianus RSY5 (K2Y) or P. kudriavzevii YSY2 (PY). These yeasts were previously identified to have the potential to effectively detoxify aflatoxin in vitro [27]. Supplemental yeasts were individually fed at the rate of 2 g/day (1 g provided 1 × 10 9 CFU) by mixing supplemental yeast with 20 g cornmeal based on our previous research [27].…”
Section: Methodsmentioning
confidence: 99%
“…These yeasts were previously identified to have the potential to effectively detoxify aflatoxin in vitro [27]. Supplemental yeasts were individually fed at the rate of 2 g/day (1 g provided 1 × 10 9 CFU) by mixing supplemental yeast with 20 g cornmeal based on our previous research [27]. Cows fed the control diet were fed 20 g corn meal without the yeast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach for the microbiological detoxification of animal feed is the screening of isolates from various environmental sources (Intanoo et al, 2018), instead of using the most widespread species, S. cerevisiae. Various bacteria and yeasts may exhibit toxin-binding or even toxin-degrading abilities, as well as biocontrol effects on toxigenic molds (Pfliegler et al, 2015) and these may be directly applied to supplement animal feed (Intanoo et al, 2018). Novel yeast species in this field include members of the genera Kluyveromyces and Pichia, both related to the widely used Saccharomyces.…”
Section: Microbial Biocontrol and Microbial Detoxification Products Fmentioning
confidence: 99%
“…P. kudriavzevii has been successfully applied as a bioadsorbent feed additive to ameliorate the negative effects of AFB 1 contamination on broiler chicken performance (Magnoli et al, 2017). Novel isolates of K. marxianus have also been proposed as bioadsorbents based on in vitro characterization (Intanoo et al, 2018). However, Battacone et al (2009) found no evidence for AFB 1 detoxification in ewes fed with Kluyveromyces lactis DYP, highlighting the need for rigorous testing of novel strains in different setups and with multiple animal species.…”
Section: Microbial Biocontrol and Microbial Detoxification Products Fmentioning
confidence: 99%